THE TECHNOLOGICAL ASPECTS OF ELEVATION OF DESIGN CHARACTERISTICS AT INDUSTRIAL USE OF THE ARTICLES OF TWO-PHASE TITANIUM ALLOYS - V. N. Fedulov (Литьë и металлургия)
Тhе technological aspects of elevation of complex of the articles mechanical characteristics, including weld ones, of (а-ф) titanium alloy BT23 in the process of thermal treating are examined. The problem of industrial use of half-finished products and products with wide palette of structures of plate type in strengthened state is studied due to investigation of advantages and deficiencies of each one.